Pendampingan Guru Madrasah dalam Pengembangan Konten Pembelajaran Digital Berbasis Nilai Keislaman dan Literasi Global - Djamila Lasaiba; Arman Man Arfa; Irvan Lasaiba; Mohammad Amin Lasaiba (Universitas Pattimura, 2025)
This community service program was conducted to enhance madrasah teachers’ competence in integrating Islamic values and global literacy into digital learning content. The background arises from teachers’ limited ability to utilize technology meaningfully and contextually in Islamic-based education. The objective is to strengthen teachers’ capacity to design, produce, and implement value-oriented digital instructional media. The method applied was Participatory Action Research through training, mentoring, classroom supervision, and the establishment of an Islamic digital teacher community. Results show significant improvements in technological mastery (+70.8%), Islamic value integration (+65.4%), and global literacy (+77.3%), along with a positive shift in teaching culture. This activity demonstrates that value-based mentoring and community collaboration effectively foster creative, reflective, and adaptive madrasah teachers in the digital era. The model implies practical policy relevance for enhancing Islamic teachers’ professionalism and can be replicated nationally.